Factors Associated with Coexisting Forms of Malnutrition (Stunting and Wasting) in Under-Five in Southeast Sulawesi (Media Kesehatan Masyarakat Indonesia, 2025)
The presence of more than one type of nutritional disorder in a person's body is called Coexisting Forms of Malnutrition (CFM). Children with CFM, such as those experiencing stunting, wasting, and underweight, 12.3 fold risk of death (CI=7.67-19.28) compared to healthy children. Southeast Sulawesi has the tenth highest prevalence of these cases. This study used secondary data based on the Indonesian Nutrition Status Survey (SSGI) 2022 with a cross-sectional design using complex sample analysis. The sample was children under five from Southeast Sulawesi Province, with a final sample size of 8,518 children analyzed. The median age of the sample was 32 months, most of them were male (50.5%), the median birth weight was 3,128.8 grams, and most of their nutritional intake was not diverse (92.1%). Bivariate analysis used chi-square, and multivariate analysis used logistic regression with a full model approach. 3.1% of children had CFM (stunting and wasting). Factors associated with this case based on bivariate analysis (p-value
Keywords: Coexisting Forms of Malnutrition; Stunting; Wasting; Children Under Five